EFISIENSI TEKNIS USAHA PENGGILINGAN PADI DI KABUPATEN CIANJUR: PENDEKATAN STOCHASTIC FRONTIER ANALYSIS - Putri, Tursina Andita; Kusnadi, Nunung; Rachmina, Dwi (Jurnal AGRISEP, 2019)
Rice agribusiness in Indonesia must be competitive so that food security can be realized. Therefore, it is necessary to improve performance in each subsystem. One of the subsystems that needs to be improved is the downstream subsystem, which is processing grain (drying and rice milling). Snowball sampling technique was applied to select 60 commercial rice mills in three sub-district. Stochastic Frontier Analysis (SFA) was used to estimate technical efficiency and to find the sources of inefficiency of the rice milling business in Cianjur Regency. The results showed that rice mills in study site was ineffecient. Factors that are affecting the technical efficiency of rice milling business in Cianjur Regency are the level of formal education, rice yield, and grain moisture content. Technical efficiency is positively corelated with the gains of rice milling business. Profits can be used for reinvestment (especially in milling machines), so that the efficiency of the rice milling business can be increased. In addition, the rice byproduct industry needs more attention to increase the benefits of the rice milling business.